The Effect of Human Resources Competence, Leadership, and Organizational Culture in Internal Control and Fraud Prevention - Umaroh, Umaroh; Setiyawati, Hari (Research Horizon, 2026)
This study aims to analyze the effect of human resource competence, leadership style, and organizational culture on the effectiveness of the internal control system and its impact on fraud prevention. This study uses a quantitative method with a survey approach. The population in this study were all employees in the Cirebon City Regional Work Unit. The sampling technique used the saturated sampling method, with a sample size of 32 respondents. Data were collected through a questionnaire that had been tested for validity and reliability. The data analysis used in this study was Smart PLS (Partial Least Square) software to test the relationship between variables. The results showed that human resource competence and organizational culture had a significant effect on the effectiveness of internal control, while leadership style had no significant effect. In addition, the effectiveness of internal control is proven to have a significant impact on fraud prevention in a positive direction. These findings provide practical implications for local governments in improving human resource training, improving organizational governance, and building a strong organizational culture to optimize the internal control system and prevent fraud in the government environment.